2018
DOI: 10.3390/molecules23092323
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiproliferative Activity of New Cyclodiprenyl Phenols against Select Cancer Cell Lines

Abstract: Six new cyclodiprenyl phenols were synthesized by direct coupling of perillyl alcohol and the appropriate phenol. Their structures were established by IR, HRMS and mainly NMR. Three human cancer cell lines—breast (MCF-7), prostate (PC-3) and colon (HT-29)—were used in antiproliferative assays, with daunorubicin and dunnione as positive controls. Results described in the article suggest that dihydroxylated compounds 2–4 and monohydroxylated compound 5 display selectivity against cancer cell lines, cytotoxicity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…The antiproliferative effect was related to induction of apoptosis and G2/M cell cycle arrest. CVN could inhibit cell invasion and the expression of the p-P38 protein at this IC 50 .…”
Section: Carvone and Its Derivativesmentioning
confidence: 87%
See 1 more Smart Citation
“…The antiproliferative effect was related to induction of apoptosis and G2/M cell cycle arrest. CVN could inhibit cell invasion and the expression of the p-P38 protein at this IC 50 .…”
Section: Carvone and Its Derivativesmentioning
confidence: 87%
“…In comparison, compounds 26b and 26c showed moderate activity. This research highlights the need for additional studies to support the therapeutical potential of these new derivatives [ 50 ].…”
Section: Perillyl Alcohol and Its Derivativesmentioning
confidence: 99%
“…Several studies have demonstrated that natural extracts have the capacity to induce cytotoxicity in cancer cells while sparing normal cells. Tis property renders them attractive candidates for the development of therapeutic agents [33][34][35][36]. A possible explanation for this diference may be the higher metabolic rates of cancer cells and the consequent increase in the demand for nutrient acquisition, which sensitize them to treatment compared with normal cells [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…This group identified several new compounds that exerted greater in vitro cytotoxicity than POH, with POH 4 -azido-D-glucoside as the most potent POH adduct. Similarly, a series of cyclodiprenyl phenols were synthesized from perillyl alcohol and synthetic phenols, and some of these meroterpenes showed strong antiproliferative and apoptosis-inducing activity against three different cancer cell lines in vitro [157]. POH was also complexed with β-cyclodextrin, which resulted in improved anticancer potency in vitro and in a sarcoma S180-induced mouse model in vivo [158].…”
Section: Perillyl Alcohol Derivatives Analogs and Conjugatesmentioning
confidence: 99%